Protective Effect of Hydroalcoholic Extract of Stachys pilifera on Oxidant-Antioxidant Status in Renal Ischemia/Reperfusion Injuries in Male Rats - Zahra Moslemi; Izadpanah Gheitasi; Amir Hossein Doustimotlagh (Journal of Toxicology)
Background. Renal ischemia-reperfusion (I/R) has a pivotal role in the progression of acute renal failure. Reactive oxygen species are considered the major constituents involved in the biochemical and pathophysiological changes that were shown during kidney I/R. The purpose of this study was to examine the renoprotective effects of Stachys pilifera ethanolic extract on oxidant-antioxidant status in renal I/R-injuries in male rats. Material and methods. Twenty-one male Wistar rats were arbitrarily distributed into 3 groups: sham control (SC), I/R, and I/R + Stachys pilifera ethanolic extract (500 mg/kg). The artery and vein of the right kidney were completely blocked, and the right kidney was completely removed in all groups. Then, the left kidney artery was blocked with suture thread for 30 minutes in only I/R and I/R + SP extract groups. Kidney function indices, oxidative stress markers, and hematoxylin and eosin staining were investigated in the plasma and kidney tissues. Results. It was shown that the urine Na and K, fractional excretion of Na and K, and protein carbonyl content markedly increased in the merely I/R group as compared to SC rats, while the administration of SP extract markedly reduced these indices (P<0.05). Also, glomerular filtration rate and total thiol meaningfully reduced in the I/R rats in contrast to the SC group, while the treatment with SP extract markedly augmented these indices (P<0.05). However, in agreement with renal function tests, SP extract had no significant effects on histopathological examinations. Conclusion. It seems that SP extract employs renoprotective effects on renal damage induced by I/R, possibly by improving of oxidant-antioxidant status in favor of the antioxidant system.